Epidemiological characterization and temporal trend of Epilepsy mortality in Brazil during the years 1999 to 2019 (Research, Society and Development, 2024)
Epilepsy is a neurological disorder characterized by the permanent predisposition of the brain to generate sudden behavioral changes and recurrent epileptic seizures. It is estimated that this neurological disorder affects more than 50 million people worldwide, appearing among the most common brain conditions, with higher incidences in developing countries, as is the case in Brazil. Thus, the present study aims to characterize the epidemiological profile and analyze the temporal trend of mortality from epilepsy in Brazil between the years 1999 to 2019. For this, an epidemiological categorization was carried out according to sociodemographic variables according to the Department of Informatics of the Unified Health System -DATASUS. To analyze the temporal trend, the joinpoint regression model was applied and the annual percentage change and its respective 95%CI confidence interval were also calculated. The South and Midwest regions had the highest mortality rates, on the other hand, the Northeast and North regions had the lowest. For sociodemographic characteristics, male gender stood out 65.12%, age group ≥ 60 24.86%; white people 46.36% and people with schooling < 8 years 35.01%. The temporal trend analysis identified an annual increase of 3.1% in the mortality rate due to epilepsy, where females and the North and Northeast regions also showed the highest percentages of annual increase in the mortality rate. Psychological problems, such as depression and anxiety, social conditions, lack of information and incorrect pharmacological treatment are factors that lead to the worsening of epilepsy. Thus, the control of mortality for epilepsy can be the effectiveness of social factors and qualified health.